Cautionary note about non-linear models in fisheries - ., Prajneshu (Indian Journal of Fisheries, 2011)
A large number of research^ papers injournals dealing with non-linear models infisheries, if nothing else, is a testimony to thefact that such models play a very importantrole in this area. For example, studies onlength-weight relationship (Ai^anasastry1989, Dcvadoss 1989. Jayasankar 1989,Premalatha 1989). estimation of fecundi^(Piska and Waghniy 1989, Hoda and Qureshi1989) and synthetic models (Kurian 1989),all involve models in which the parametersappear in a non-linear manner.